Evaluating the Socioecological Classroom in Full-Service Schools: A Whole-School Approach to the Inclusive Education Context in South Africa - Sifiso Emmanuel Mbelu; Mbulaheni Obert Maguvhe (Education Sciences)
This paper evaluates the socioecological classroom in the context of a whole-school approach to inclusive education, which has evolved beyond the traditional classroom setting. Inclusive education calls for a paradigm shift to accommodate learners previously marginalised, with the classroom transforming into an ecosystem. The socioecological paradigm steers away from the notion that psychological and physiological elements are the main causes of disability. The importance of addressing multiple layers of influence is emphasised to create a supportive and inclusive learning environment. First, Bronfenbrenner’s Ecological Systems Theory, which emphatically explains how a learner’s development is influenced by the systems in the environment that surrounds them, and then Foucault’s Theory of Power and Knowledge, in which power and knowledge are interconnected and inseparable, with power being exercised through the creation and control of knowledge, guided this study. A qualitative approach was adopted, and semi-structured interviews, focus group discussions and non-participant observation were used to collect data. Phenomenological analysis was used to analyse the data from these data-collecting instruments. It was found that learners with disabilities need support at home, with imbalances being found in the power–knowledge relations between teachers and parents, and teachers occupying a superior position regarding academic knowledge. Some teachers still believe in the Medical-Deficit Model. A strengths-based approach should rather be adopted. Strategies for enhancing community–school collaboration that balances teacher–parent power dynamics should be explored.